Leukocyte Heterogeneity in Adipose Tissue, Including in Obesity. Issue 11 (22nd May 2020) - Weinstock, Ada; Moura Silva, Hernandez; Moore, Kathryn J.; Schmidt, Ann Marie; Fisher, Edward A.
Abstract : Adipose tissue (AT) plays a central role in both metabolic health and pathophysiology. Its expansion in obesity results in increased mortality and morbidity, with contributions to cardiovascular disease, diabetes mellitus, fatty liver disease, and cancer. Obesity prevalence is at an all-time high and is projected to be 50% in the United States by 2030. AT is home to a large variety of immune cells, which are critical to maintain normal tissue functions. For example, γδ T cells are fundamental for AT innervation and thermogenesis, and macrophages are required for recycling of lipids released by adipocytes. The expansion of visceral white AT promotes dysregulation of its immune cell composition and likely promotes low-grade chronic inflammation, which has been proposed to be the underlying cause for the complications of obesity. Interestingly, weight loss after obesity alters the AT immune compartment, which may account for the decreased risk of developing these complications. Recent technological advancements that allow molecular investigation on a single-cell level have led to the discovery of previously unappreciated heterogeneity in many organs and tissues. In this review, we will explore the heterogeneity of immune cells within the visceral white AT and their contributions to homeostasis and pathology.